Bubbles, banking and monetary policy - Shim, Jae Hun (Journal of Financial Stability, 2025)
This paper lays out a quantitative macroeconomic model with rational risk-adjusted asset bubbles and banks. The model features an imperfect financial market structure and allows bubble assets within banks. We shed light on the channels by which a sudden burst of asset bubbles leads to a recession through the banking system and evaluate “leaning against the wind” monetary policy associated with bubble volatility and welfare. Our main findings call for monetary policy rules to preemptively stabilize intermediate asset prices rather than the bubbles.